Asymptotic Stability of Fractional Stochastic Neutral Differential Equations with Infinite Delays - Sakthivel, R.; Revathi, P.; Mahmudov, N. I. (Hindawi Ltd, 2013)
We study the existence and asymptotic stability in pthmoment of amild solution to a class of nonlinear fractional neutral stochastic differential equations with infinite delays in Hilbert spaces. A set of novel sufficient conditions are derived with the help of semigroup theory and fixed point technique for achieving the required result. The uniqueness of the solution of the considered problem is also studied under suitable conditions. Finally, an example is given to illustrate the obtained theory.
Keywords: Exponential Stability; Mild Solutions